Post‐viraemic detection of bovine ephemeral fever virus by use of autogenous lymphoid tissue‐derived bovine primary cell cultures. Issue 1 (January 2017) - Barigye, R; Davis, S; Hunt, R; Hunt, N; Walsh, S; Elliott, N; Dyrting, K; Weir, R; Melville, LF
Abstract : Background: The potential tissue replication sites and specific cell types that support in vivo virus survival beyond the acute phase of bovine ephemeral fever virus (BEFV) infection have not been fully defined in cattle. To clarify the knowledge gap, tissue specimens were tested after collection from an adult steer necropsied 1 week after acute BEF. Case report: Significant necropsy findings included fibrinoproliferative synovitis in the stifle joints and fibrin clot‐laden fluid in serous body cavities. Moderate numbers of infiltrating neutrophils were demonstrated in sections of the prefemoral lymph nodes and haemal node, and lymphoid hyperplasia in the spleen, haemal node and prefemoral lymph nodes. Viral RNA was detected by qRT‐PCR in fresh spleen, haemal node, prefemoral lymph node, synovial fluid and in several spleen‐derived cell cultures. BEFV was isolated from autogenously derived splenic primary cell cultures 6 days after cessation of viraemia, and characteristic bullet‐shaped virions were confirmed by electron microscopy of an ultrathin haemal node section. In sections of the spleen, haemal node and other tissues, immunohistochemistry demonstrated BEFV antigens that were intracellularly associated with probable histiocytic cells. Conclusion: BEFV has preferential tropism for bovine lymphoid tissues and the spleen and haemal node may be potential sites for post‐viraemic virus replication.